The development of digital literacy smart e-book (CERI) as a resource for learning digital literacy skills in elementary schools - Maharani, Anggun Kusuma Budi; Rahmawati, Fitri Puji (Universitas Ahmad Dahlan, 2023)
This Research and Development (R&D) study focuses on creating Smart Digital Literacy E-books to serve as a valuable learning resource for enhancing digital literacy skills among elementary school students. Employing the ADDIE model, encompassing the Analysis, Design, and Development stages, the research seeks to address the critical need for effective digital literacy education in elementary schools. The subjects of this investigation comprised grade VI students at SDN 02 Palur. To gather comprehensive data, a combination of interviews, observations, and questionnaires was employed. Interviews with resource persons provided insights into students' current digital literacy skills, while observations were conducted to understand their digital literacy activities at school. Additionally, a questionnaire, administered by a validation expert, assessed the effectiveness of the CERI E-book. The validation tests yielded encouraging results, with language validation scoring 87.5%, subject validation at 83.33%, and media validation at an impressive 95.83%. Feedback from the feasibility test, conducted among students, affirmed the CERI E-book's suitability for educational use. Students highlighted its interactivity, ease of understanding, and comprehensive content, reinforcing its efficacy as a learning resource. In conclusion, the outcomes of this research and development endeavor underscore the high suitability of the CERI E-book for fostering digital literacy skills in elementary school students. The interactive features and comprehensive content make it a valuable contribution to the field of digital literacy education